Pengaruh Human Relation, Kecerdasan Emosional Dan Lingkungan Kerja Terhadap Kinerja Karyawan LPD Desa Adat Kerobokan - Suryadnya Diputra, I Komang; Mustika, I Nyoman (Fakultas Ekonomi Universitas Gresik, 2023)
Human resources contained in a company is one of the most valuable assets owned by an organization, because humans are the only resource that can drive other resources. So it is necessary to do the management or development that aims to create productive human beings. This study aims to determine and analyze the influence of human relations, emotional intelligence and work environment on the performance of LPD employees in Kerobokan Traditional Village, Badung. The population in this study were all employees of the LPD in the Kerobokan Traditional Village, Badung. Sampling in this study using the census sampling method, obtained 56 respondents. The analytical method used is multiple linear regression analysis, descriptive statistical analysis, research instrument test, classical assumption test, determination analysis and t test.The results of the study show that human relations, emotional intelligence and work environment have a positive and significant effect on employee performance at the Kerobokan Traditional Village LPD, which means that the better the human relations, emotional intelligence and work environment, the higher the employee's performance. The leadership of the LPD in the Kerobokan Badung Traditional Village should improve work quality, such as establishing good communication among fellow employees, controlling employee awareness of their own emotions about moods and thoughts and improving a conducive work environment to increase employee work efficiency